Penerapan Outdoor Mathematics Aktivity bagi Guru SD di KKG Gugus 1 Kecamatan Sirenja Kabupaten Donggala - Anggraini, Anggraini; Sugita, Gandung (Penerbit Goodwood, 2024)
Purpose: The aim of community service activities in 2023 is to help elementary school teachers in KKG Gugus 1 Sirenja sub-district Donggala district in implementing outdoor mathematics activities with elementary school students for measurement material. Methodology: : This activity takes the form of teacher training with implementation methods including: (1) lecture/presentation, (2) question and answer, and (3) group work. The props used for this activity were measuring tape, rope, LKPD, and objects outside the classroom. After the activity, the teachers filled out a questionnaire to assess the achievements of the activities conducted by the Mathematics Education Study Program service team from the Mathematics and Natural Sciences Education Department at FKIP Tadulako University. Results: Based on discussions during the activity and the results of the questionnaire, information was obtained that all activity participants had never applied mathematics learning outside the classroom. The material presented provided a good understanding of the Outdoor Mathematics Activity, and the results of the activity helped teachers in carrying out activities outside the classroom. Conclusions: Teachers gain a clear understanding of how to implement enjoyable and contextual mathematics learning. This activity successfully fosters students' motivation and engagement in learning, as well as creates a more meaningful learning atmosphere compared to conventional methods that focus solely on memorization. Limitations: The study may be limited by the participants' prior lack of experience with outdoor mathematics activities, and the short duration of the training may not provide a comprehensive understanding of the implementation. Contribution: This community service activity contributes to enhancing the understanding and skills of elementary school teachers in implementing outdoor mathematics activities, thereby potentially improving student engagement and learning outcomes in mathematics.